The Increased lncRNA MIR503HG in Preeclampsia Modulated Trophoblast Cell Proliferation, Invasion, and Migration via Regulating Matrix Metalloproteinases and NF-κB Signaling. (30th July 2019) - Cheng, Dan; Jiang, Shan; Chen, Jiao; Li, Jie; Ao, Liangfei; Zhang, Ying
Abstract : Background . Preeclampsia (PE) is a pregnancy-related syndrome characterized by hypertension and proteinuria after the 20 th week of gestation. The long noncoding RNAs (lncRNAs) have been recently discovered for their roles in the pathogenesis of PE. This study is aimed at determining the expression of lncRNA MIR503 host gene (MIR503HG) in PE placental tissues and exploring the molecular mechanism underlying MIR503HG-mediated trophoblast cell proliferation, invasion, and migration. Methods . The expression level of MIR503HG in placental tissues, HTR-8/SVneo, and JEG3 cells was determined by quantitative real-time PCR; western blot detected the relevant protein expression levels in HTR-8/SVneo and JEG3 cells; flow cytometry determined cell apoptosis and cell cycle of HTR-8/SVneo and JEG3 cells; trophoblast cell proliferation, invasion, and migration of HTR-8/SVneo and JEG3 cells were measured by CCK-8, transwell invasion, and wound healing assays, respectively. Results . The highly expressed MIR503HG was detected in PE placental tissues compared to normal placental tissues. MIR503HG overexpression suppressed cell proliferation, invasion, and migration of HTR-8/SVneo and JEG3 cells, while knockdown of MIR503HG increased trophoblast cell proliferation, invasion, and migration. Flow cytometry results showed that MIR503HG overexpression induced apoptosis and caused cell cycle arrest at the G0 /G1 phase, while MIR503HG knockdown had the opposite actions in HTR-8/SVneo and JEG3 cells. Western blot assay results showed that MIR503HG overexpression suppressed the matrix metalloproteinase-2/-9 and the snail protein expression and increased the E-cadherin expression in trophoblast cells. In addition, MIR503HG overexpression suppressed the NF- κ B signaling pathway by inhibiting the phosphorylation of I κ B α and the nuclear translocation of NF- κ B signaling subunit p65. On the other hand, MIR503HG knockdown played an opposite role in these protein expression levels. Conclusion . Our results showed that MIR503HG inhibited the proliferation, invasion, and migration of HTR-8/SVneo and JEG3 cells, which may be related to the pathogenesis of PE.